Improving Energy Access to the Urban Poor in Developing Countries - The Energy and Resources Institute (World Bank, Washington, DC, 2014)
The case studies documented in this report aim to inform the energy access community (including practitioners, civil society groups, project planners, end users) about best practices of successful energy access initiatives targeted at slum dwellers. Eight case studies focusing on electrification and household energy were selected from India, Bangladesh, Colombia and Brazil, all countries that have had varying success in providing access to modern energy services for slum dwellers. The cases had to meet all or some of the following criteria: 1) limited to developing countries; 2) demonstrate innovative methods of improving energy access, including collaborative stakeholder engagement; 3) at least one example of small local energy service providers; 4) contributed to community development by promoting local skill development and income generation; and 5) representative of electricity and different sources of household energy. The case studies describe the existing conditions in the slum, type of energy service provided, the key characters involved, conditions for success, and replicable factors. Common barriers to energy access were identified and impact on the lives of slum dwellers, were also discussed.